Membrane technology and engineering for water purification : application, systems design and operation - Singh, Rajindar (Butterworth-Heinemann, 2015)
Membrane Technology and Engineering for Water Purification, 2nd edition is written in a practical style with emphasis on: process description; key unit operations; systems design and costs; plant equipment description; equipment installation; safety and maintenance; process control; plant start-up; and operation and troubleshooting. It is supplemented by case studies and engineering rules-of-thumb. The author is a chemical engineer with extensive experience in the field, and his technical knowledge and practical know-how in the water purification industry are summarized succinctly in this new.